Total dominator coloring of circulant graphs Cn(a, b) - Jalilolghadr, Parvin,; Kazemi, Adel P.,; Khodkar, Abdullah, (Utilitas Mathematica, 2020)
The circulant graph Cn(S) with connection set S ⊆ {1,2, • • •,n} is the graph with vertex set V = { 1, . . ., n} and two vertices x,y are adjacent if |x — y| ∈ S. In this paper, we will calculate the total dominator chromatic number of the circulant graph Cn({a,b}) when n ≥ 6, gcd(a,n) = 1 and a-1b ≡ 3 (mod n). © 2019 Utilitas Mathematica